Analisis Tindak Tutur Lokusi pada Daftar Putar “Kisah Tokoh Inspiratif” dalam Kanal Youtube Zenius - Fina Fadhilatul Amalia; Gisella Orlanova Ramadhanti; Aulia Rahayu; Muhamad Taufiq Hamdani; Iyas Rahmawati; Asep Purwo Yudi Utomo; Rossi Galih Kesuma (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Living humans cannot be separated from language to communicate. Communication is carried out by expressing what the speaker will convey to his speech partner through speech acts. Speech acts themselves have various types, starting from locutionary, illocutionary, and perlocutionary. The main focus of this research is the use of locutionary speech acts in the